2013
DOI: 10.1093/mnras/stt1113
|View full text |Cite
|
Sign up to set email alerts
|

Orbital anisotropy in cosmological haloes revisited

Abstract: The velocity anisotropy of particles inside dark matter (DM) haloes is an important physical quantity, which is required for the accurate modelling of mass profiles of galaxies and clusters of galaxies. It is typically measured using the ratio of the radialto-tangential velocity dispersions at a given distance from the halo centre. However, this measure is insufficient to describe the dynamics of realistic haloes, which are not spherical and are typically quite elongated. Studying the velocity distribution in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 46 publications
3
35
0
1
Order By: Relevance
“…iv) Finally, we explored a description of velocities in which the anisotropy of the intra-halo velocity distribution is preserved. The anisotropy of the velocity dispersion has been shown to be key to interpret and model kinematic mass data (Wojtak et al 2013;Kafle et al 2014) and can thus lead to further corrections in the amplitude of fingers of god, especially if the anisotropy depends on the properties of the galaxy samples. To construct these galaxy samples we preserve the radial component of the intra-halo velocity of each galaxy, and randomize the direction of the tangential component.…”
Section: Possible Improvementsmentioning
confidence: 99%
“…iv) Finally, we explored a description of velocities in which the anisotropy of the intra-halo velocity distribution is preserved. The anisotropy of the velocity dispersion has been shown to be key to interpret and model kinematic mass data (Wojtak et al 2013;Kafle et al 2014) and can thus lead to further corrections in the amplitude of fingers of god, especially if the anisotropy depends on the properties of the galaxy samples. To construct these galaxy samples we preserve the radial component of the intra-halo velocity of each galaxy, and randomize the direction of the tangential component.…”
Section: Possible Improvementsmentioning
confidence: 99%
“…Unless explicitly mentioned, we focus on our fiducial tagging model, although the results presented do not depend significantly on this assumption. Dark matter halos within ΛCDM have radially biased orbits (Wojtak et al 2009(Wojtak et al , 2013 with apocentres that are significantly larger than the pericentres. Numerical simulations have shown that subhalos (and therefore satellite galaxies inhabiting those subhalos) inherit such elliptical orbits (Sales et al 2007;Iannuzzi & Dolag 2012), an effect that contributes to the disruption and lowering of star formation in satellites, even for those seemingly today in the outskirts of groups and clusters.…”
Section: Orbits and Dynamics Of Gcsmentioning
confidence: 99%
“…Unfortunately, the method presented here also depends on the assumption that the velocity ellipsoid is spherical. This introduces an additional bias to the anisotropy parameter as discussed in Wojtak et al (2013) for tracers in cluster sized haloes. Replacing the Jeans equations with the Virial equations enables us to include information on the shape of the LOS velocity distribution without reference to β , the anisotropy between the shape of the radial and tangential distributions.…”
Section: Spherical Symmetry and Dynamic Equilibriummentioning
confidence: 99%